THE ANALISYS OF CATFISH (Pangasius sutchi) AQUACULTURE IN THE POND OF KOTO MESJID VILLAGE XIII KOTO KAMPAR DISTRICT KAMPAR REGENCY RIAU PROVINCE - Falentria Anglina; Hendrik '; M. Ramli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on December 2014. This study aims to determine how much of the investment, benefit, feasibility and problems faced by fish farmers in the aquaculture of Catfish (Pangasius sutchi) in the pond of Koto Mesjid Village. The method use in this research is a stratified random sampling method with respondens are 13 farmers were divided into 3 stratas.The results of this research indicate that business investment smoke catfish farming in the pond for aquaculture strata I is Rp. 53.905.057,-/unit aquaculture, for strata II the require Rp.135.942.250,-/unit aquaculture and investments for the aquaculture of strata III is Rp.229.361.250,-/unit aquaculture. The value BCR of Catfish farmers in the Koto Mesjid village is between 1.08 until 1.13, value of FRR is 16.02% until 25.08% and the value of PPC 7.97 period until 12.48 period. Based on the results of the analysis of the work done then concluded that the cultivation of the most financially feasible to be developed is the cultivation of strata III by using the BCR value of 1.13, FRR amounted to 25.08%/years and PPC are 7,97 period or 3.99 years. Constraints faced by farmers in the enterprise is feed prices tend to be relatively high and the presence of pests and diseases that attack the fish in the pond.Keyword: Koto Mesjid village, Investment, BCR, FRR, PPC, Catfish